A Primer on Cell and Molecular Biology. - Running, Mark (Momentum Press, 2015)
The study of cells is fundamental to biological inquiry, yet few cells are big enough to be seen with the naked eye. That means cells must be studied indirectly, most obviously through the use of microscopes, but also through molecular techniques. Since we can't directly observe cells, we form models (conceptualizations) of cell structures and processes that fit observable and empirical data. Such conceptualizations are intellectual leaps forward in understanding how life works and separate cell and molecular biology from more traditional observations that preceded these disciplines.